FRI0107 Lung ultrasound for the diagnosis of interstitial disease in rheumatoid arthritis. (23rd January 2014) - Torzillo, D.; Antivalle, M.; Birocchi, S.; Columpsi, D.; Ditto, M.C.; Battellino, M.; Sarzi-Puttini, P.; Norsa, A.; Montano, N.; Cogliati, C.
Abstract : Background: Interstitial lung disease (ILD) is one of the most frequent extra-articular manifestation of rheumatoid arthritis (RA). Up to 50% of RA patients will develop lung disease during their life and an excess of mortality has been demonstrated for this group (1-2). Early diagnosis of ILD can modify its natural history improving the prognosis. Currently, the diagnosis, stadiation and follow-up of ILD are achieved by high resolution computed tomography (HRCT), wich is reportedly as accurate as lung biopsy. Nevertheless, HRCT is an expensive technique, and exposes the patient to the risks associated with ionizing radiations. In the last ten years, lung ultrasound (LUS) has been demonstrated to be a useful non invasive diagnostic tool to assess pulmonary disease in many conditions; in particular, in presence of interstitial lung fibrosis vertical artefacts generated by thickened interlobular septa are detectable; these artifacts arise from the pleural line, are synchronous with respiratory movements and are called B-lines. Objectives: The aim of this study was to assess if pulmonary LUS performed by an expert physician may detect and quantify lung fibrosis in RA patients. Results obtained by LUS were compared with HRCT data. Methods: Thirty-eight RA patients undergoing lung HRCT for clinical suspicion of ILD were evaluated. In a first session, an expert physician performed LUS; B-lines were counted by scanning anterior and posterior pulmonary fields, following anatomical lines. As previously reported in literature, LUS was considered negative (absence of fibrosis) when the total number of B lines was less than or equal to ten, positive (presence of fibrosis) when total B lines were more than 10. Moreover, the total number of B-lines (echographic score) was correlated with the Warrick Score, a previously described point score, based on HRCT images, for grading fibrosis. In 28.patients a second examination by means of a hand-carried device was performed by a physician who underwent two three-hours training sessions for the recognition of B lines; anterior and posterior scans were conducted and just a qualitative (negative or positive) response was obtained. Sensitivity and specificity were calculated in respect to CT for both the echographic sessions; the correlation between echographic and HRCT scores was calculated using Spearman test. Results: Total B-lines highly correlated with Warrick Score (r=0, 72). Sensitivity and specificity for LUS performed by expert physician were 92% and 56% respectively, while sensitivity and specificity for hand carried LUS were 88% and 50% respectively. Conclusions: These data demonstrate that LUS shows a very high sensitivity for the detection of lung fibrosis either when a standard equipment is used by an expert physician as well as when short-trained operator performs the examination by means of a hand carried device, thus strongly supporting the use of LUS as a screening test for ILD in RA patients. Moreover, the strong correlation between echographic and HRCT scores indicates LUS, a non invasive, repeatable and low cost technology, as a useful tool for the grading and follow up of pulmonary fibrosis. References: Mark J. Hamblin et al, Pulmonary Medicine 2011 Bongartz T et al, Arthritis Rheum. 2010 Disclosure of Interest: None Declared